Perspective towards 1Bestarinet Frog Virtual Learning Environment (VLE) among secondary school Students of Sekolah Agama Menengah Tengku Ampuan Jemaah, Shah Alam / Adnin Nabihah Zawawi - Zawawi, Adnin Nabihah (Faculty of Education, 2014)
E-learning has become the solution that is growing from day to day. The use of online elearning in education at the school is increasing. It is important to identify students’ perspective towards e-learning so that teaching and learning process can take place positively. This study was aimed to investigate the perspective of secondary school students towards a specific type of online e-learning, that of IBestarinet Frog Virtual Learning Environment (VLE) System. The sample used in this research was 30 respondents of secondary school students from Sekolah Agama Menengah Tengku Ampuan Jemaah. The instrumentation used in this research was a questionnaire. From the finding of the research, most students favour the Frog VLE. The highest perspective that influence students to favour the Frog VLE is because it is easy to use. Besides, from this research, most of the students found difficulty when participating in the Frog VLE System because the computers provided at the school are not enough for all students.